2018
DOI: 10.1590/1678-98652018000100009
|View full text |Cite
|
Sign up to set email alerts
|

Educational training of nutritionists in Public Health Nutrition: A systematic review

Abstract: , as well as in the gray literature. The steps of systematic search followed the recommendations of the Preferred Reporing Itens for Systematic Reviews and Meta-Analysis. Eligibility criteria included studies on the Public Health training in Nutrition Undergraduate courses, whose subjects were students, educators, and professionals who practice in the field of Nutrition. A total of 633 articles were identified, of which, 66 were eligible for reading and analysis of the full text and 12 were included in the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
11
0
3
Order By: Relevance
“…Several authors report that, despite advances in the professionalization of nutritionists in general and specifically for Collective Health, traditional practices oriented towards curative assistance with a biological focus still predominate, often far from an integral approach, which considers complexity inherent to the food and nutritional phenomenon (Medeiros et al, 2014;Neves et al, 2014;Aguiar & Costa, 2015;Almeida, Oliveira, Monteiro, Medeiros, & Recine 2018). Also, fragmented curricular structures with vertical transmission of knowledge predominate, making dialogue with other sciences difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors report that, despite advances in the professionalization of nutritionists in general and specifically for Collective Health, traditional practices oriented towards curative assistance with a biological focus still predominate, often far from an integral approach, which considers complexity inherent to the food and nutritional phenomenon (Medeiros et al, 2014;Neves et al, 2014;Aguiar & Costa, 2015;Almeida, Oliveira, Monteiro, Medeiros, & Recine 2018). Also, fragmented curricular structures with vertical transmission of knowledge predominate, making dialogue with other sciences difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionists who were more satisfied at work were those who classified their knowledge in food service as excellent. For instance, Almeida et al [34] conducted a systematic review and observed the importance of the relationship between theory and practice, the dimensions of teaching, research and extension, and practical activities and internships for the development of skills and competencies of nutritionists who work in the public health area.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment will take place through the Joanna Briggs Institute's critical appraisal tools, using a speci c checklist for each type of study found. From the assessment of methodological quality based on the tools of the Joanna Briggs Institute, studies with up to 49% of a rmative responses will be classi ed as studies with a high risk of bias, studies with a rmative responses between 50% and 69% will be classi ed as studies with moderate risk of bias and studies with 70% or more of a rmative responses will be classi ed as studies with low risk of bias 16 .…”
Section: Bias Risk and Quality Assessmentmentioning
confidence: 99%